URBAN SUSTAINABILITY IN ANCIENT OASIS CITIES - THE CASE OF KSAR LICHIANA IN ALGERIAN DESERT - Abdelkader Merided (International Journal of Innovative Technologies in Social Science, 2024)
The current research aims to determine the extent to which the cities of the ancient oases applied the concepts of sustainability in their planning dimension. To achieve this goal, the theoretical foundations of sustainable urban unit planning are identified, constituting the first part of the study. In the second part, the characteristics of the ancient oasis cities in the Ziban region, in the eastern Algerian desert, are highlighted, taking the city of Lichana as a case study. It then proceeds to analyze its urban principles and explore its planning vocabulary from the perspective of sustainability concepts, forming the final part. The research concludes that the cities of the ancient oases applied the concepts of sustainability early on in their planning dimension, within their three economic, social, and environmental pillars. The study breaks down these concepts by identifying the theoretical foundations of sustainable urban units, then examining the characteristics and planning vocabulary of a specific oasis city, Lichana. This analysis reveals that these ancient oasis cities integrated principles of economic, social, and environmental sustainability from their very conception.